Податково-правовий статус юридичних осіб-учасників офшорної діяльності - Зоріна, О. І.; Зорина, О. И.; Zorina, О. (My University, 2012)
For basis of this article the study of concept of status of resident of country of registration was accepted, which is a main condition for the receipt of tax and other privileges, given one or another favorable jurisdiction. In this connection, by an author were studied basic, known in a tax right, going near determination of status of resident or nonresident of company on territory of country of registration.
Зоріна О. І. Податково-правовий статус юридичних осіб-учасників офшорної діяльності /О. І. Зоріна // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 323-333.
Keywords: резидент країни реєстрації; статус резидента; статус нерезидента компанії; офшорна діяльність; резидент страны регистрации; статус резидента; статус нерезидента компании; офшорная деятельность; a resident of the country of registration; resident status; the status of non-resident companies